Alcohol misuse in older people: heavy consumption and protean presentations. Issue 12 (15th November 2006) - Mehta, Milan M; Moriarty, Kieran J; Proctor, David; Bird, Mary; Darling, Wendy
Abstract : Background: Alcohol misuse, especially binge drinking in young people, and alcoholic liver disease are major public health concerns. However, alcohol misuse in older people is underestimated and often goes undetected. Objective: To document alcohol consumption and clinical presentation of alcohol misuse in hospital inpatients aged ⩾60 years. Methods: 208 inpatients aged ⩾60 years, referred to the alcohol liaison nurse between 1998 and 2003 at the Royal Bolton Hospital, Bolton, UK, were assessed for sex, alcohol intake, primary and secondary reasons for admission, and other concurrent health problems and death. Results: 90% of men drank >21 units weekly and 93% of women drank >14 units weekly. Median weekly alcohol intake was 78.5 units for men and 47 units for women. Acute intoxication, falls, circulatory problems and alcoholic liver disease were the main primary reasons for admission. Neglect or malnutrition, alcoholic liver disease and hypertension were the main secondary reasons and concurrent health problems. 30% of patients died between 1998 and 2003. Conclusion: In inpatients aged ⩾60 years who were referred to the alcohol liaison nurse in a district general hospital, heavy alcohol consumption, often to very high levels, was characteristic in both men and women and was associated with a wide variety of primary and secondary clinical presentations, including death.